O ensino/aprendizagem na extensão rural na concepção da teoria histórico cultural - Laluce, Cícero Rogerio Henrique (2022)
Rural extension has always been an important activity for the development process of the countryside, leading research advances to improve agricultural activities. Since its beginning, the political-pedagogical project of the universities has been used to carry out the process of spreading out such knowledge, a fact that has comes along with extension since then and is in the core of the discussion of this present work. These political-pedagogical projects did not allow extension to implement teaching-learning processes with the aim of making rural subjects aware of their reality and able to change it significantly in their own favor. In this work, we sought, through historical materialism, in a bibliographic review, to characterize the history of rural extension in Brazil, with emphasis on these processes, identifying and critically analyzing, in well-defined stages, the inconsistencies that jeopardized the success of these processes, having the historical-cultural theory as a theoretical reference. This characterization is divided into three stages: initially, a period aimed at improving the quality of life of farmers, mixing aspects of the way of life and production, called “welfare humanism”; a second historical moment, termed “productivist diffusionism”, with the objective of increasing production and productivity through a rural extension guided by the dissemination of technology packages, the responsiveness of farmers and the guarantee of agricultural credit; the third stage is characterized by a “critical humanism”, focused on sustainable production based on the principles of agroecology and liberation theology, under a participatory approach. We tried to demonstrate, in the three stages, that there is no consistent theory that provides a didactic-pedagogical and/or methodological basis so that processes of development of superior cognitive skills can be carried out, since, at no time, is scientific knowledge conceptually constructed, not managing, therefore, to lead individuals to the autonomy of thought, nor to an understanding of reality on a whole. In this work, we propose the historical-cultural theory of teaching-learning process as an alternative to mitigate this problem. In this proposal, the building of conceptual thinking based on scientific knowledge contributes to the individual´s ability not only to overcome the existing problems in the "modern" way of doing agriculture, but to provide an "education" that adapts or shapes man to its present time and prepare him for the challenges of the future.